TMIC-45. RADIATION THERAPY-INDUCED EPIGENETIC REWIRING PROMOTES GLIOMA PHENOTYPIC PLASTICITY - Deepthi Muthukrishnan, Sree (Neuro Oncol, 2019)
Therapeutic failure and relapse of glioblastoma (GBM) tumors is attributed to a fraction of chemo- and radiation-resistant glioma stem cells (GSCs). Growing evidence indicates that GSCs and tumor cells elicit phenotypic plasticity in response to radiation-therapy (RT) such as de-differentiation and acquisition of a GSC-like state, and epithelial-to- mesenchymal transition (EMT) leading to more aggressive tumors and relapse. Preliminary findings from our laboratory indicate that RT also promotes vascular transdifferentiation of glioma cells, and the transdifferentiated vascular cells are essential for tumor growth in vivo. Together, these studies suggest that RT alters the dynamic equilibrium between “stemness” and “differentiation” states of the tumor cells. Transition between different cellular states or phenotypes required global alterations in chromatin landscape and associated transcriptional changes, and this epigenetic rewiring process is observed in several stages of oncogenesis and metastatic transformation. We hypothesized that epigenetic rewiring occurs in GBM tumor cells that survive radiation-induced DNA damage altering their cell fate that leads to diverse phenotypic outcomes such as EMT, acquisition of stem-like state and vascular transdifferentiation. Preliminary findings from bulk ATAC- and RNA-sequencing of patient-derived gliomasphere lines show that RT increases chromatin accessibility, and reduces expression of several histone components and their chaperones. Gene ontology and transcription factor motif analyses of open chromatin regions showed an enrichment of factors and terms related to pluripotency, vascular specification and stem cell differentiation. Furthermore, single-cell RNA-sequencing of radiated and control tumor cells also showed an increase in vascular markers expressing-clusters, and reduction in expression of histone components post radiation supporting our hypothesis that RT causes epigenetic rewiring in glioma cells leading to diverse phenotypic outcomes including vascular transdifferentiation. Ongoing experiments are aimed at determining the precise molecular mechanism by which RT causes chromatin rewiring, and identifying candidates involved in this process for therapeutic targeting.